Extraction and Application of Eco-Friendly Natural Dyes Obtained from Libyan Local Plants on Textiles - Eman Alsaeh; Najmeddin Ellali; Amjaad Alseah; Waad Altroak; Nooralhuda Atia (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. In the present study, experiments were carried out to use an extract isolated from parts of plants (shell of almond, bark, and pods of carob, the flower of reichardia tingitana L., and leaves of olive, guava, and malvus with aqueous as a natural dye. Methods. The dye potential of the extracts was evaluated by dyeing on cotton, silk, and nylon fabrics under normal dyeing conditions using selected synthetic and natural mordants. The synthetic mordant was ferrous chloride whereas the natural mordants were lemon peel and pomegranate rind and tested for their colour fastness to washing and rubbing properties. Results. The results found to be for each mordant was selected for light and dark shades. The washing and rubbing fastness of the dyed samples were also evaluated, giving fair to excellent fastness grades and this evaluation is also useful for textile industries. Conclusion. Dye extracted from plants can be used as a textile dye with selected natural mordants